Pertanggungjawaban Pelaku Tindak Pidana Narkotika dan Tindak Pidana Pencucian Uang - Ivan Kurniawan (Faculty of Law, Universitas Lampung, 2020)
The narcotics crime is one of the extraordinary crimes so that it is specifically regulated in act of Law Number 35 Year 2009 concerning Narcotics. The perpetrators and other parties involved in narcotics crime certainly understand the severe consequences of what they do. In connection with the above problem, there is one interesting decision to be reviewed and analyzed, which has been decided by the panel of judges is the decision number: 124 / Pid.Sus / 2016 / PN.TJK in which the perpetrator commits two offenses at once so that the sentence could be sentenced whether it has been be fair. This study will focus on legal issues, namely knowing the responsibility of the perpetrators of narcotics and money laundering crimes. analyze the court's decision Number: 124 / Pid.Sus / 2016 / PN.TJK whether it has fulfilled a sense of justice that is beneficial. This study uses a Normative Juridical approach by analyzing a court decision. As for the results of the study found that: According to the analysis of researchers seen from the criminal responsibility has fulfilled the elements of error, the ability to be responsible, evil inner attitude, and there is no reason to forgive. Court Decision Number: 124 / Pid.Sus / 2016 / PN.TJK has fulfilled a useful sense of justice. Based on research shows that the verdict given is considered fair because the defendant's actions have damaged the nation's generation and remembering that the defendant's actions committed two offenses namely violating Article 131 of Law Number 35 Year 2009 concerning Narcotics and Article 5 paragraph (1) letter c of the Act Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes. As for the suggestions that can be submitted in this study, it is better for the police in an effort to prevent the circulation of narcotics and money laundering so that they coordinate well with the financial transaction analysis tracking center and also the national land agency so that the assets of drug dealers or traffickers can be properly tracked.